PENGARUH PENYULUHAN KESEHATAN TERHADAP PENGETAHUAN MASYARAKAT MENGENAI KESIAPSIAGAAN BENCANA GEMPABUMI DESA JAMBUDIPA RW 15 - Agus Sudiana (Jurnal Kesehatan Rajawali, 2020)
Background: Indonesia is an archipelago located at the confluence of 3 tectonic plates which has the potential to be prone to earthquakes. Disaster preparedness is an effort to face the possibility of a disaster in order to avoid casualties, property loss, and changes in the community's life order. Research Purposes: to determine the effect of health education on public knowledge about earthquake disaster preparedness in Jambudipa Village Rw 15 West Bandung Regency 2020. Research Methods: The design used in this study was Quasy Experiment, using a pre-post test design in one group (one-group pre-post test design). The number of samples taken was 35 research subjects, with a purposive sampling method. Research Results: The results showed that before being given health education, from the 35 respondents studied, 51.4% had insufficient knowledge, 31.4% had sufficient knowledge, 17.1% had good knowledge and public knowledge after providing health education, it was found that 14.3% had insufficient knowledge, 28.6% had sufficient knowledge and 57.1% had good knowledge. Conclusion: based on the results of the calculation of the Wilcoxon statistical test, there is a significant effect between before and after the provision of health education on public knowledge about earthquake disaster preparedness. This is indicated by the significant value = 0.000 which is smaller than the alpha value = 0.05 (p <α).